CPC-002 A Multicentre Retrospective Study to Evaluate the Economic Impact of the Prescribing Models For Trastuzumab in the Piemonte Region. (12th March 2013) - Barilà, DA; Bianco, A; Bustreo, S; Donadio, M; Rosso, S; Cattel, F
Abstract : Background: In recent years, there has been a rapid and constant increase in the costs of cancer treatment but, with limited health care resources, it is essential to consider the economic implications of different health interventions. Purpose: To evaluate the economic impact of the different prescribing models for trastuzumab on overall costs for breast cancer treatments in the Piemonte Region. Materials and Methods: We systematically reviewed the MEDLINE-indexed, English-language literature to identify published, peer-reviewed economic analyses of trastuzumab in HER2± treatment of breast cancer. We rated study quality as per the Drummond criteria. Direct medical and unit costs were calculated from the perspective of a Regional health care system. We derived patient data by consulting a Regional administrative database and screening by File F File C and SDO for each patient treated in 2010. To obtain valid data, it is necessary to combine the data from this study into a single model, with an epidemiological measure from the Piemonte Cancer Registry. It is recommended to use an empirical Bayesian analysis to conduct this study because there is no single estimator for the parameters. Results: The search strategy identified 948 articles, of which 340 were citations. From the 608 remaining, 23 articles were considered suitable for full review based on the inclusion criteria. Of these, 15 considered adjuvant trastuzumab treatment only, seven examined metastatic breast cancer treatment and one considered treatment with trastuzumab beyond progression. The analysis of the accuracy of information provided by the information systems showed us that there was only 40% correspondence with the administrative database within Molinette Hospital. Conclusions: Preliminary results confirm the difficulty of obtaining accurate data from the administrative systems. We hope to obtain precise data on trastuzumab prescribing, and thus offer complementary information to cost-effectiveness analysis before the launching of a generic drug. No conflict of interest.